ALISIS YURIDIS PENGENAAN HONORARUM ATAS JASA-JASA NOTARIS DI KOTA MEDAN - Keumala Meutia (Jurnal Perspektif Hukum, 2022)
As a public official, a notary does not receive a salary from the government but has the right to withdraw an honorarium from services provided based on Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Positions, and the Notary Code of Ethics. The position of a notary makes it possible to serve requests from presenters regarding work other than making authentic deeds by receiving the agreed honorarium. The data used are primary data and secondary data. The data collection method used is library research and field research. The data collection tool used is interviews.The results of the study show that the notary's honorarium needs to be regulated because it helps determine the minimum standard of the notary's honorarium will greatly help maintain the professionalism of the notary in carrying out his profession and prevent competition between fellow notaries and there are no violations of the law. So that the creation of justice for notaries in receiving notary services rates. The application of the Notary's honorarium in Medan City in its implementation is not always in accordance with the applicable regulations, due to the Notary's reasons in determining the honorarium, namely factors from the Notary himself, competition between Notaries, the economic value of the deed, the existence of levies, requests and interests of clients, families , life experience, friends, organization, spirituality, situational factors and other factors originating from the environment of the Notary concerned, which are taken into consideration by the Notary in determining the value of the honorarium services he provides and the agreement of both parties.